Low grade appendiceal mucinous neoplasm : A case series of 12 cases with review of literature (Journal of Pathology of Nepal, 2024)
Background: Low-grade appendiceal mucinous neoplasm (LAMN) is a rare epithelial tumour of the appendix, accounting for 1% of gastrointestinal neoplasms and found in less than 0.3% of appendectomy specimens. It is histologically characterized by a villous or flat proliferative mucinous epithelium with low-grade cytological features. Prognosis depends on the presence of neoplastic epithelium and mucin outside the appendix, which increases the risk of peritoneal dissemination.  The Present case series reviews 12 LAMN cases diagnosed between 2020 and 2024, analyzing clinical, radiological, and histopathological findings. Cases were staged using the AJCC 8th edition, emphasizing the importance of standardized examination for accurate diagnosis and prognosis.Results: The median patient age was 55 years, with a slight female predominance. Abdominal pain was the most common symptom. All cases exhibited intraluminal mucin with low-grade mucinous epithelium. Two cases had extra-appendiceal mucin (pT3 and pT4a), while the remaining were confined to the appendix (pTis). No recurrence was observed.Conclusions: LAMN remains a diagnostic and prognostic challenge, requiring thorough histopathological evaluation. Standardized staging and long-term follow-up are crucial for optimal management.